The Moderating Role of Audit Risk in the Use of Information Technology on Auditors' Professional Skepticism - kezia agustin Nugrahaningrum; Ety Meikhati; Erna Chotidjah Suhatmi (International Journal of Indonesian Business Review, 2026)
This study aims to analyze the influence of information technology use on auditors' professional skepticism and examine the moderating role of audit risk in this relationship. This study is motivated by the inconsistency of research results regarding the influence of information technology use on auditors' professional skepticism, so it is necessary to examine situational factors that can strengthen this relationship. The study uses a quantitative approach with primary data obtained through distributing questionnaires to 80 auditors at 13 Public Accounting Firms in the Surakarta and Yogyakarta areas selected using a purposive sampling technique. Data analysis was performed using Moderated Regression Analysis (MRA) with the help of SPSS version 26. The results show that the use of information technology has a positive effect on auditors' professional skepticism. In addition, audit risk is proven to moderate this relationship by strengthening the influence of information technology use on auditors' professional skepticism. These findings indicate that the effectiveness of information technology utilization in increasing professional skepticism will be higher when auditors face a high level of audit risk. This study provides an empirical contribution in explaining the role of audit risk as a situational factor that strengthens the relationship between the use of information technology and auditors' professional skepticism.